Pentaho 8 reporting for Java developers create pixel-perfect analytical reports using reporting tools - Corti, Francesco (Packt Publishing, 2017)
Create reports and solve common report problems with minimal fuss. About This Book Use this unique book to master the basics and advanced features of Pentaho 8 Reporting. A book showing developers and analysts with IT skills how to create and use the best possible reports using the Pentaho platform. Written with a very practical approach: full of tutorials and practical examples (source code included). Who This Book Is For This book is written for two types of professionals and students: Information Technologists with a basic knowledge of Databases and Java Developers with medium seniority. Developers will be interested to discover how to embed reports in a third-party Java application. What You Will Learn The basics of Pentaho Reporting (Designer and SDK) and its initial setup. Develop the most attractive reports on top of a wide range of data sources. Perform detailed customization of layout, parameterization, internationalization, behaviors, and more for your custom reports developed with Pentaho Reporting. Integrate Pentaho reports into third-party Java application with full control over interactions, layout, and behavior in general. Use Pentaho reports in the other components of the Pentaho Suite (BA Platform and PDI). In Detail This hands-on tutorial, filled with exercises and examples, introduces the reader to a variety of concepts within Pentaho Reporting. With screenshots that show you how reports look at design time as well as how they should look when rendered as PDF, Excel, HTML, Text, Rich-Text-File, XML, and CSV, this book also contains complete example source code that you can copy and paste into your environment to get up-and-running quickly. Updated to cover the features of Pentaho 8, this book will teach you everything you need to know to build fast, efficient reports using Pentaho. If your interest lies in the technical details of creating reports and you want to see how to solve common reporting problems with a minimum of fuss, this is the book for you. Style and approach A step-by-step guide covering technical topics relating to environments, best practices, and source code, to enable the reader to assemble the best reports and use them in existing Java applications.
Online resource; title from title page (viewed October 3, 2017)
Keywords: Business report writing -- Data processing; Java (Computer program language); Style commercial; Informatique; Java (Langage de programmation); Business report writing; Data processing